Adaptation and validation of the research task distractor scale in Peruvian university students - Óscar Mamani-Benito; Jhoanna Marilú Llaguento Zurita; Olga Lidia García Vásquez; Fiorella Guerrero; Wilter C. Morales-García; Josué Edison Turpo Chaparro (My University, 2023)
Unconventional distractions such as electronic devices are stimuli that divert attention during study tasks, especially those related to scientific research exercises in undergraduate education. In the absence of precise instruments to measure this phenomenon, the objective was to adapt and validate the Scale of Distractions in Research Tasks among Peruvian university students. The study is classified as an instrumental cross-sectional design, involving 1,003 university students aged between 18 and 47 years ( M = 20.93, SD = 4.30) from three regions of Peru (Coast, Highlands, and Jungle), selected through convenience sampling. Content validity was assessed using Aiken’s V coefficient, internal structure was examined through confirmatory factor analysis, and reliability was measured using the Omega coefficient. The results indicated that the judges positively evaluated the 5 items (V > 0.70), the internal structure confirmed the original model with satisfactory fit indices ( χ 2 (2) = 5.47, p = 0.187, CFI = 0.998, RMSEA = 0.023, and SRMR = 0.010), and the reliability was acceptable (ω = 0.86). In conclusion, the Peruvian version of the Scale of Distractions in Research Tasks has demonstrated to be a valid and reliable instrument, characterized by its brevity and a unifactorial structure.
Keywords: Confirmatory factor analysis; Reliability (semiconductor); Adaptation (eye); Scale (ratio); Psychology; Structural equation modeling; Task (project management); Jungle; Applied psychology; Computer science; Statistics; Mathematics education; Mathematics; Geography; Engineering; Cartography; Systems engineering; Archaeology; Physics; Quantum mechanics; Neuroscience; Power (physics); Confirmatory factor analysis; Reliability (semiconductor); Adaptation (eye); Scale (ratio); Psychology; Structural equation modeling; Task (project management); Jungle; Applied psychology; Computer science; Statistics; Mathematics education; Mathematics; Geography; Engineering; Cartography; Social Sciences Psychology Social Psychology Motivation and Self-Concept in Sports; Social Sciences Social Sciences Education Social Skills and Education; Social Sciences Social Sciences Education Educational Methods and Psychological Studies